2017
DOI: 10.31234/osf.io/ayd3t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why the A/AN prediction effect may be hard to replicate: A rebuttal to DeLong, Urbach & Kutas (2017)

Abstract: In our recent publication “How robust are prediction effects in language comprehension? Failure to replicate article-elicited N400 effects” (Ito, Martin, & Nieuwland, 2016a), we report two experiments which failed to replicate existing ERP evidence for prediction as reported in C. D. Martin et al. (2013), whose study resembled DeLong, Urbach, and Kutas (2005; from hereon DUK05). DeLong, Urbach, and Kutas (2017; from hereon, DUK17) recently published a commentary which depicts our publication as a case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…An exploratory Bayes factor analysis of the N400-cloze correlation suggested that any effect size for phonological prediction would be quite small. These studies raise the question of how robust the a/an article effects are (for more discussions about the replicability of these effects, see DeLong, Urbach, & Kutas, 2017;Ito, Martin, & Nieuwland, 2017b;Nieuwland et al, 2018;Yan, Kuperberg, & Jaeger, 2017). As with gender prediction, there has been inconsistency in the ERPs reported for phonological mismatch.…”
Section: Prediction Of Phonological Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…An exploratory Bayes factor analysis of the N400-cloze correlation suggested that any effect size for phonological prediction would be quite small. These studies raise the question of how robust the a/an article effects are (for more discussions about the replicability of these effects, see DeLong, Urbach, & Kutas, 2017;Ito, Martin, & Nieuwland, 2017b;Nieuwland et al, 2018;Yan, Kuperberg, & Jaeger, 2017). As with gender prediction, there has been inconsistency in the ERPs reported for phonological mismatch.…”
Section: Prediction Of Phonological Informationmentioning
confidence: 99%
“…Another possible reason for the lack of phonological-mismatch effects relates specifically to the a/an manipulation. The a/an phonological rule is not realised by agreement between the article and the noun but between the article and the initial phoneme of the next word, and the occurrence of an intervening word is very common in English (67% written, 30% spoken, Ito et al, 2017b;Yan et al, 2017). If people make phonological predictions only for the next upcoming word, then the probability that the expected noun comes directly after the article should play an important role in determining when or whether such phonological information should be pre-activated.…”
Section: Reliability Of Gender and Phonological Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed a rather robust N400 effect after the onset of the noun (e.g., 'kite'), but only one lab replicated the N400 effect after the onset of the article (e.g., 'a'). This finding suggests that the weak prediction effect of word-form information (e.g., phonology) might only occur occasionally and such an effect might require a large sample size to be detected (Ito et al, 2017b;Nieuwland et al, 2018). Moreover, some bilingual studies have also observed an unstable pattern of phonological prediction effect for native speakers (L1).…”
Section: Is Phonological Prediction Necessary In Comprehension?mentioning
confidence: 97%
“…Incorporating these findings, there is now no LAN, the N400 is elicited early, by both syntactic and semantic conditions, and the P600 is elicited late, by both syntactic and semantic conditions as well. Nevertheless, the functional significance of both the N400 and the P600, in terms of the underlying cognitive processes, is still a topic of hot debate (e.g., Shen et al [ 6 ] and Ito et al [ 7 ] ). In this context, [ 6 ] have shown, that a semantic P600 paradigm source localized to executive rather than classical language areas, thus supporting an extra-linguistic rather than an intra-linguistic interpretation of the P600.…”
Section: Introductionmentioning
confidence: 99%